High Level of ATP Citrate Lyase Expression in Human and Rat Pancreatic Islets - MacDonald, M. J.; Longacre, M. J.; Warner, T. F.; Thonpho, A. (Hormone and Metabolic Research, 2013)
A comparison of an enzyme’s level in pancreatic islets with its level in other body tissues can give clues about the importance of a metabolic pathway in the islets. ATP citrate lyase plays a key role in the pyruvate citrate shuttle, as well as for the synthesis of short chain acyl-CoAs and lipid, and its level in human and rat pancreatic islets relative to other tissues has not been previously reported. We compared the level of ATP citrate lyase mRNA and enzyme activity in pancreatic islets of humans and rats and the INS-1 832/13 cell line to levels in liver, a lipid synthesizing organ, and also kidney. The mRNA level was much higher in human islets and rat islets than in liver and kidney of the same genus and the enzyme activity was 8-fold and 12-fold higher in islets of humans and rats, respectively, compared to liver of the same genus. These data support other evidence that indicates ATP citrate lyase is important for the pyruvate citrate shuttle and lipid synthesis in insulin secretion.